Impact of Spiritual and Social Competence Development on Teachers’ Professional Performance - Akhyar, Yundri; Sutrawati, Eli; Ningsih, Wirda (Paedagogie, 2026)
This study aims to analyze the levels of spiritual competence, social competence, and professional performance among teachers and to examine the contribution of spiritual and social competencies to professional performance. A quantitative survey design was employed involving 120 teachers as research participants. Data were collected using structured questionnaires and analyzed through descriptive statistical techniques to identify trends across variables. The findings reveal that teachers demonstrate high levels of spiritual and social competence, which positively support their professional performance. The results indicate that professional performance is not solely determined by pedagogical expertise but is also influenced by internal dimensions such as meaning, ethical integrity, and value orientation, as well as relational dimensions including communication and collaboration. This study contributes to the development of educational science by reinforcing a multidimensional competency framework that integrates spiritual and social competencies as strategic determinants of sustainable teacher effectiveness. The findings provide empirical support for holistic teacher development models that combine character-based formation with collaborative professional growth to enhance educational quality.